Pemanfaatan Biocarrier Dari Limbah Sedotan Plastik Sebagai Media Tumbuh Chlorella sp. Dalam Moving Bed Biofilm Reactor (MBBR) Untuk Penyisihan Bahan Polutan Dalam Limbah Cair Domestik - Isabella Amalia Denisa Putri; Shinta Elystia; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Moving Bed Biofilm Reactor (MBBR) is a biological processing technology with two microorganism culture processes, namely inherent growth and suspended growth. Microalgae Chlorella sp. is one microorganism that can be used in biological processing. Microalgae can stick to the surface of the media because microalgae produce extracellular soluble Algae Products (SAP) consisting of proteins and polysaccharides that are useful in the process of attaching microalgae to the surface of the bio carrier media. This study aims to set aside the parameter of ammonia in domestic wastewater. In this study, the media used were made of spiral hoses and plastic straws with a length of 10 mm and a diameter of 12.7 mm. Processing with MBBR uses variations in media volume that is 15%, 30%, and 45% and with variations in contact time 0, 1, 3, 5, and 7 days. The results showed the highest removal efficiency of ammonia in 30% media volume variations on the 7th day respectively 89.82%.Keywords: Biocarrier, Chlorella sp., Domestic Liquid Waste, MBBR